x+3(4x+2)=7x-1

Simple and best practice solution for x+3(4x+2)=7x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+3(4x+2)=7x-1 equation:


Simplifying
x + 3(4x + 2) = 7x + -1

Reorder the terms:
x + 3(2 + 4x) = 7x + -1
x + (2 * 3 + 4x * 3) = 7x + -1
x + (6 + 12x) = 7x + -1

Reorder the terms:
6 + x + 12x = 7x + -1

Combine like terms: x + 12x = 13x
6 + 13x = 7x + -1

Reorder the terms:
6 + 13x = -1 + 7x

Solving
6 + 13x = -1 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
6 + 13x + -7x = -1 + 7x + -7x

Combine like terms: 13x + -7x = 6x
6 + 6x = -1 + 7x + -7x

Combine like terms: 7x + -7x = 0
6 + 6x = -1 + 0
6 + 6x = -1

Add '-6' to each side of the equation.
6 + -6 + 6x = -1 + -6

Combine like terms: 6 + -6 = 0
0 + 6x = -1 + -6
6x = -1 + -6

Combine like terms: -1 + -6 = -7
6x = -7

Divide each side by '6'.
x = -1.166666667

Simplifying
x = -1.166666667

See similar equations:

| 10=-2.5(z-3.1) | | 4(-2)-(3X-3)+4= | | a^2+24am^2x^2+144m^4x^4=0 | | 10=0.03c-9.1 | | e5-14=8 | | -116=2(8n-2) | | abc+ghi=ghi | | (6x-5y)+(3x+3y-2)= | | 5x=-4y+50 | | 5xsquared+3=23 | | 3(x+1)=4(2-3x)-17 | | 8x-64-3x=16 | | 7x+7x=35 | | x^3-2x^2-19x+18=0 | | 100x=1x+5 | | 15-13+2=4 | | 13n-9=29 | | -2a-8=-26 | | 6v=x+2y | | 100x=5x+1 | | -4x+8x-62=54 | | -5d-21=54 | | 8x-2(3x-x)=6x-7x | | 6-5x+2x=-30 | | 5(w-3)=7w-23 | | -10+15x=-9x+2 | | 5y-14=15 | | c9-8=17 | | 0.47= | | 5n-7=25 | | 0.8x+9=4.8x-16 | | 4x-2y=130 |

Equations solver categories